2019
DOI: 10.1029/2018jd029701
|View full text |Cite
|
Sign up to set email alerts
|

A Decadal Data Set of Global Atmospheric Dust Retrieved From IASI Satellite Measurements

Abstract: Aerosol is an important component of the Earth's atmosphere, affecting weather, climate, and diverse elements of the biosphere. Satellite sounders are an essential tool for measuring the highly variable distributions of atmospheric aerosol. Here we present a new algorithm for estimating atmospheric dust optical depths and associated retrieval uncertainties from spectral radiance measurements of the Infrared Atmospheric Sounding Interferometer (IASI). The retrieval is based on the calculation of a dust index an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 139 publications
(182 reference statements)
3
57
2
Order By: Relevance
“…The amplitude of the QBO signal is found to be stronger for QBO30 than for QBO10 in the LSt, which is in good agreement with studies from other instruments for the total O 3 (e.g. Baldwin et al, 2001;Steinbrecht et al, 2006;Frossard et al, 2013;Coldewey-Egbers et al, 2014) and from IASI in the troposphere (Wespes et al, 2017). The smaller amplitude of O 3 response to QBO10 in the LSt compared to the MUSt is again in agreement with previous studies that reported changes in the phase of the QBO10 response as a function of altitude with a positive response in the upper stratosphere and destructive interference in the middle-low stratosphere (Chipperfield et al, 1994;Brunner et al, 2006).…”
Section: Drivers Of O Natural Variationssupporting
confidence: 89%
See 2 more Smart Citations
“…The amplitude of the QBO signal is found to be stronger for QBO30 than for QBO10 in the LSt, which is in good agreement with studies from other instruments for the total O 3 (e.g. Baldwin et al, 2001;Steinbrecht et al, 2006;Frossard et al, 2013;Coldewey-Egbers et al, 2014) and from IASI in the troposphere (Wespes et al, 2017). The smaller amplitude of O 3 response to QBO10 in the LSt compared to the MUSt is again in agreement with previous studies that reported changes in the phase of the QBO10 response as a function of altitude with a positive response in the upper stratosphere and destructive interference in the middle-low stratosphere (Chipperfield et al, 1994;Brunner et al, 2006).…”
Section: Drivers Of O Natural Variationssupporting
confidence: 89%
“…As for the QBO, the strong SF dependence at polar latitudes in the LSt with zonal asymmetry in the O 3 response reflects the influence of the polar vortex strength and of stratospheric warmings and is in good agreement with previous results (e.g. Hood et al, 1997;Zerefos et al, 1997;Labitzke and van Loon, 2000;Steinbrecht et al, 2003;Coldewey-Egbers et al, 2014). It is also worth noting that because only one solar cycle is covered, the QBO and SF effects could not be completely separated because of their strong interaction (e.g.…”
Section: Drivers Of O Natural Variationssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the NN computing efficiency permits the processing of the entire IASI/Metop-A and -B observational time series. Other advantages of the ANNI retrieval scheme are specifically discussed by Clarisse et al (2019) and Whitburn et al (2016). Examples of regional CH 3 COOH (and superimposed HCOOH) column distributions from individual days of IASI/Metop-A and -B observations are shown in Figure 1.…”
Section: Neural Network Retrievalmentioning
confidence: 99%
“…Further, these sensors allow making observations at nighttime. Currently, global long term data sets of AOD are available from infrared sensors like the Atmospheric InfraRed Sounder (AIRS) and the Infrared Atmospheric Sounding Interferometer (IASI), onboard the polar-orbiting Aqua and MetOp satellites, respectively (DeSouza-Machado et al, 2010;Capelle et al, 2018;Clarisse et al, 2019;Popp et al, 2016). They can additionally provide dust layer mean altitude because infrared channels are sensitive to different levels of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%